PENGARUH E-SERVICE QUALITY, KESADARAN MEREK, KEPERCAYAAN, WORD OF MOUTH, DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN: Studi Pada Pelanggan Tiktok Shop - Murhadi, Werner Ria; Reski, Eva Cahaya (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
This study aims to analyze e-service quality, brand awareness, trust, word of mouth, and satisfaction with customer loyalty at TikTok shops (study on TikTok shop customers). Data were collected through a survey with 151 respondents. The study used primary data obtained from the distribution of online questionnaires. The respondents are Indonesian people who have made purchases on the TikTok Shop application. Non-probability sampling was used for sampling. This research uses a structural equation modeling approach. In this study, it was found that there is a positive influence between E-service Quality and customer trust. The study also found that E-service Quality had a positive effect on customer satisfaction and a positive effect on Brand Awareness on customer trust. Other findings are that there is a positive influence on Brand Awareness on customer satisfaction, and the results also found a positive influence on customer satisfaction on customer loyalty. Meanwhile, Word of Mouth's effect on customer trust was not found, and there was no significant effect between customer trust and customer loyalty.